Composition and Energy Band–Modified Commercial FTO Substrate for In Situ Formed Highly Efficient Electron Transport Layer in Planar Perovskite Solar Cells. (28th January 2019) - Sun, Haoxuan; Zhou, Yu; Xin, Yu; Deng, Kaimo; Meng, Linxing; Xiong, Jie; Li, Liang
Abstract: Perovskite solar cells (PSCs) have received much attention and with them a power conversion efficiency (PCE) of over 22% has been achieved. Electron transport layers (ETLs) based on metal oxide materials play an important role in transferring electrons and reducing back recombination. However, existing fabrication approaches are generally waste too many materials and consume too much energy for commercial application. Here, a brand new plasma preannealing procedure is proposed that can replace the traditional ETL preparation process and alleviate the above‐mentioned problems. A pure SnO2 phase in situ formed on the fluorine‐doped tin oxide (FTO) surface can be obtained at room temperature by only 15 min oxygen plasma assisted reaction without postheating treatment. It enables the precise control of compositions, defects, and energy levels of band at the surface of FTO substrate, resulting in a prominent PCE of 20.39% with excellent stability and reproducibility. This simple and efficient source‐free fabrication technology provides a versatile platform for the manufacture of PSCs in the future. Abstract : Highly efficient SnO2 ETL for planar perovskite solar cells is produced by using a plasma treatment procedure. This procedure enables the precise control of composition, defects, and band energy levels at the interface between FTO and perovskite. This simple and efficient source‐free fabrication technology provides a versatile platform for the manufacture of PSCs.